Development of Student Worksheets Based on REACT on Quadrilateral Material - Andyah Agustin; Yusuf Fuad (MATHEdunesa, 2022)
Some studies have showed that students still struggle to solve problems involving quadrilaterals, particularly kites and rhombuses. One of learning strategy that can be used is REACT strategy, which emphasizes teaching and learning of constructivist principles, performs one of the suitable learning strategies. This research aims to describe the process of developing and producing REACT-based student worksheets which satisfy the following criteria: valid, practical, and effective. This study used the 4D model (Define, Design, Develop and Disseminte) and utilizing a One-Shot Case Study research design. The study involves 32 students of the grade VII of SMPN 1 Mojosari during the even semester of the academic year 2019-2020. Test, interview, questionnaire are utilized to obtain the data of this study. The results emphasize that the LKS is valid with the average total validity criteria for the LKS with respect to circumference and area formulas, as well as for rhombus and kite are 3.25; 3.71; and 3.57 respectively. The LKS satisfies the practical criteria with a few minor with the average score on the learning observation analysis is 3.13. Finally, The LKS fulfills also as the effective criteria with the student’s questionnaire responses indicate that the student response is positive with an average percentage of 89.4% and the percentage of classical learning completeness or student learning test is 78%. So that this LKS can be used as a source and medium of learning by junior high school mathematics teachers in learning quadrilateral material, especially rhombuses and kites. Keywords: Student worksheet, quadrilateral ,REACT